Covering Soybean Leaves With Cellulose Nanofiber Changes Leaf Surface Hydrophobicity and Confers Resistance Against Phakopsora pachyrhizi - Saito, Haruka; Yamashita, Yuji; Sakata, Nanami; Ishiga, Takako; Shiraishi, Nanami; Usuki, Giyu; Nguyen, Viet Tru; Yamamura, Eiji; Ishiga, Yasuhiro (Frontiers in Plant Science, 2021)
Asian soybean rust (ASR) caused by Phakopsora pachyrhizi, an obligate biotrophic fungal pathogen, is the most devastating soybean production disease worldwide. Currently, timely fungicide application is the only means to control ASR in the field. We investigated cellulose nanofiber (CNF) application on ASR disease management. CNF-treated leaves showed reduced lesion number after P. pachyrhizi inoculation compared to control leaves, indicating that covering soybean leaves with CNF confers P. pachyrhizi resistance. We also demonstrated that formation of P. pachyrhizi pre-infection structures including germ-tubes and appressoria, and also gene expression related to these formations, such as chitin synthases (CHSs), were significantly suppressed in CNF-treated soybean leaves compared to control leaves. Moreover, contact angle measurement revealed that CNF converts soybean leaf surface properties from hydrophobic to hydrophilic. These results suggest that CNF can change soybean leaf surface hydrophobicity, conferring resistance against P. pachyrhizi, based on the reduced expression of CHSs, as well as reduced formation of pre-infection structures. This is the first study to investigate CNF application to control field disease.